Epithelial-Mesenchymal Transition in Colorectal Carcinoma: Comparison Between Primary Tumor, Lymph Node and Liver Metastases - Pavlič, Ana; Urh, Kristian; Štajer, Katarina; Boštjančič, Emanuela; Zidar, Nina (Frontiers in Oncology, 2021)
There is emerging evidence suggesting that epithelial-mesenchymal transition (EMT) and mesenchymal-epithelial transition (MET) play an important role in colorectal carcinoma (CRC), but their exact role remains controversial. Our aim was to analyze the miR-200 family as EMT markers and their target genes expression at invasive tumor front and in nodal and liver metastases. Sixty-three formalin-fixed paraffin-embedded tissue samples from 19 patients with CRC were included. Using a micropuncture technique, tissue was obtained from central part and invasive front of the primary tumor, and nodal and liver metastases. Expression of the miR-200 family and their target genes CDKN1B, ONECUT2, PTPN13, RND3, SOX2, TGFB2 and ZEB2 was analyzed using real-time PCR. We found miR-200 family down-regulation at invasive front compared to central part, and up-regulation of miRNA-200a/b/c and miR-429 in metastases compared to invasive front. At invasive front, TGFB2 was the only gene with inverse expression to the miR-200 family, whereas in metastases inverse expression was found for ONECUT2 and SOX2. CDKN1B, PTPN13 and ZEB2 were down-regulated at invasive front and up-regulated in metastases. Our results suggest the involvement of partial EMT at invasive tumor front, and partial MET in metastases in CRC, based on miR-200 family and its target genes expression.